Comparison of human chromosome 19q13 and syntenic region on mouse chromosome 7 reveals absence, in man, of 11.6 Mb containing four mouse calcium-sensing receptor-related sequences: relevance to familial benign hypocalciuric hypercalcaemia type 3. - Hannan, F; Nesbit, M; Turner, J; Stacey, J; Cianferotti, L; Christie, P; Conigrave, A; Whyte, M; Thakker, R (2010)
Familial benign hypocalciuric hypercalcaemia (FBHH) is a genetically heterogeneous disorder that consists of three designated types, FBHH1, FBHH2 and FBHH3, whose chromosomal locations are 3q21.1, 19p and 19q13, respectively. FBHH1 is caused by mutations of a calcium-sensing receptor (CaSR), but the abnormalities underlying FBHH2 and FBHH3 are unknown. FBHH3, also referred to as the Oklahoma variant (FBHH(Ok)), has been mapped to a 12cM interval, flanked by D19S908 and D19S866. To refine the location of FBHH3, we pursued linkage studies using 24 polymorphic loci. Our results establish a linkage between FBHH3 and 17 of these loci, and indicate that FBHH3 is located in a 4.1 Mb region flanked centromerically by D19S112 and telomerically by rs245111, which in the syntenic region on mouse chromosome 7 contains four Casr-related sequences (Gprc2a-rss). However, human homologues of these Gprc2a-rss were not found and a comparative analysis of the 22.0 Mb human and 39.3 Mb mouse syntenic regions showed evolutionary conservation of two segments that were inverted with loss from the human genome of 11.6 Mb that contained the four Gprc2a-rss. Thus, FBHH3 cannot be attributed to Gprc2a-rss abnormalities. DNA sequence analysis of 12 other genes from the interval that were expressed in the parathyroids and/or kidneys did not detect any abnormalities, thereby indicating that these genes are unlikely to be the cause of FBHH3. The results of this study have refined the map location of FBHH3, which will facilitate the identification of another CaSR or a mediator of calcium homeostasis.